The prevalance of and factors associated with intra-abdominal hypertension on admission Day in critically Ill pediatric patients: A multicenter study - (:unkn) unknown (W B SAUNDERS CO-ELSEVIER INC, 2015)
Purpose: To investigate admission prevalence of intraabdominal hypertension (IAH) and to determine clinical and laboratory characteristics on admission day associated with IAH in critically ill pediatric patients. Materials and Methods: One hundred thirty newly admitted critically ill pediatric patients were included. Intraabdominal pressure (IAP) was measured 4 times (every 6 hours) with the bladder pressure method. Data included the demographics, diagnostic category, pediatric logistic organ dysfunction score and pediatric risk of mortality score II, clinical concomitant factors, and conditions potentially associated with increased intra-abdominal pressure. Results: Seventy patients (56.1%) had a normal IAP (<= 10 mmHg, mean IAP [mmHg] 7.18 +/- 1.85), while 60 patients (43.9%) had IAP >10 mmHg (mean IAP [mmHg] 15.46 +/- 5.21). Hypothermia frequency, lactate levels, number of patients with oligo-anuria, and mechanical ventilation requirement were higher among patients with IAH compared to patients without IAH (both, P<.05). Hypothermia (OR, 3.899; 95% CI, 1.305-11.655; P<.03) and lactate levels (OR, 1.283 for eachmmol/L increase; 95% CI, 1.138-1.447; P<.001) were only significantly associated with IAH. Conclusions: Intra-abdominal hypertension seems to affect nearly half of newly admitted critically ill pediatric patients. Lactate level and the presence of hypothermia seem to be the independent predictors of the presence of IAH. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Intra-abdominal pressure; Lactate; Hypothermia; Abdominal compartment syndrome; Organ dysfunction; Oligo-anuria; ABDOMINAL COMPARTMENT SYNDROME; INTERNATIONAL-CONFERENCE; PERFUSION-PRESSURE; CHILDREN; DEFINITIONS; LAPAROTOMY; EXPERTS; PH